Internal homonegativity among men having sex with men: a comparative cross-national study - Shestakovskyi, O.; Kasianczuk, M.; Trofymenko, O.; Chepurko, G.; Djuma, V.; Howell, S. (Социология: теория, методы, маркетинг, 2019)
The paper studies internalized homonegativity (IH) and its predictors among men who have sex with men (MSM) in 12 countries of Eastern Europe and Central Asia (EECA). Internalized homonegativity (sometimes called internal homophobia) is a negative attitude to own same-sex attractions. It arises when gays and other people with homosexual attractions interiorize predominant negative attitudes and assumptions about homosexuals and homosexuality. Досліджено інтерналізовану гомонегативність (ЫГ) та її чинники серед чоловіків, які практикують секс з чоловіками (ЧСЧ) у 12 країнах Східної Європи та Центральної Азії (СЄЦА). Інтерналізована гомонегативність (яку інколи називають внутрішньою гомо-фобією) є негативним ставленням до власних одностатевих потягів. Вона виникає тоді, коли геї та інші люди з гомосексуальними потягами засвоюють панівні негативні настанови й переконання про гомосексуалів і гомосексуальність. Исследована интернализированная гомонегативность (ИГ) и ее факторы среди мужчин, практикующих секс с мужчинами (МСМ) в 12 странах Восточной Европы и Центральной Азии (ВЕЦА). Интернализированная гомонегативность (которую иногда называют внутренней гомофобией) является негативным отношением к собственным однополым влечениям. Она возникает тогда, когда геи и другие люди с гомосексуальными влечениями усваивают господствующие негативные установки и убеждения о гомосексуалах и гомосексуальности.